Predictors of allergen sensitization in Singapore children from birth to 3 years. Issue 1 (December 2016) - Loo, Evelyn; Sim, Jordan; Goh, Anne; Teoh, Oon; Chan, Yiong; Saw, Seang; Kwek, Kenneth; Gluckman, Peter; Godfrey, Keith; Bever, Hugo; Chong, Yap; Lee, Bee; et al.
Abstract Background Immune responses in allergic diseases begin with allergen sensitization, which usually occurs in childhood. Allergen sensitization involves a complex interplay of genetic and environmental factors, and sensitization patterns may change with age. Objective To determine the predictors of allergen sensitization in the first 3 years of life in the growing up in Singapore towards healthy outcomes (GUSTO) prospective birth cohort study. Methods Interviewers collected information on demographics, family history of allergy, social and lifestyle factors, and the child's health. We analyzed data from 849 children who completed skin prick testing (SPT) to inhalant allergens (house dust mites:Dermatophagoides pteronyssinus, Dermatophagoides farinae, andBlomia tropicalis ) and food allergens (egg, peanut and cow's milk) to assess risk factors for allergen sensitization at 18 months. To ensure that clinical phenotypes preceded allergen sensitization, we also analyzed data from 649 children who had a negative skin prick test at 18 months and completed skin prick testing at 36 months. Results We observed a significant association between eczema reported before 18 months and a positive SPT at 18 months [aOR 4.5 (1.9–10.7)]. Ninety-five (14.6 %) children with negative SPTs at 18 months developed positive tests at 36 months. Onset of eczema before 18 months was associated with an increased risk of new allergen sensitization at 36 months among children non-sensitized at 18 months [aOR 3.4 (1.2–9.3)]. An association was seen between wheeze reported before 18 months and new allergen sensitization at 36 months [aOR 3.2 (1.1–9.1)]. We found no significant association, however, between rhinitis reported before 18 months and new allergen sensitization at 36 months. Conclusions Early onset of eczema and wheeze are risk factors for later allergen sensitization, suggesting a possible increased susceptibility to allergen exposure through an impaired skin barrier or defective airway epithelium. Trial registration NCT01174875 Registered 1 July 2010, retrospectively registered